Edge-selectively phosphorus-doped few-layer graphene as an efficient metal-free electrocatalyst for the oxygen evolution reaction. Issue 88 (17th October 2016) - Xiao, Zhaohui; Huang, Xiaobing; Xu, Lei; Yan, Dafeng; Huo, Jia; Wang, Shuangyin
Abstract : Edge-selectively phosphorus-doped few-layer graphene (G–P) was synthesized and investigated for OER electrocatalysts with high performance. Abstract : The development of efficient, stable and cost-effective electrocatalysts for the oxygen evolution reaction (OER) is the key for water splitting. Carbon-based nanomaterials have found significant applications as metal-free OER electrocatalysts. In this study, for the first time, edge-selectively phosphorus-doped graphene (G–P) was synthesised for OER electrocatalysts. The G–P catalyst reached a current density of 10 mA cm −2 at a small overpotential of 330 mV for the OER with a Tafel slope as low as 62 mV dec −1, which is superior to most of the carbon-based electrocatalysts reported to date.